Electrodeposition and Properties of Tin Seleno Sulphide - Lee, Tien Ping (2005)
Thin film semiconductors such as tin seleno sulphide films are considered important technological materials because of their potential applications in solar cells, infrared detectors and lasers. These thin films can be prepared by electrodeposition because of its simple, low cost and easy to control parameters. In this research, tin seleno sulphide thin films have been electrodeposited potentiostatically from aqueous solution containing SnCl₂, Na₂SeO₃ and Na₂S₂O₃ on titanium substrate. Disodium salt of ethylenediaminetetraacetic acid (Na₂-EDT A) was used as a complexant to improve the adhesion of the deposited film on the substrate. Cyclic voltammetry was performed to elucidiate the electrodic processes occurred and determine the potential range for electrodeposition. The effect of parameters such as bath temperatures, the presence of EDT A, deposition potentials, electrolytes concentrations, deposition times, pH, and annealing temperatures on the film properties were studied. The deposited films were characterized by powder X-ray diffiaction (PXRD), scanmng electron microscopy (SEM), energy dispersive X-ray analysis (ED AX) and linear sweep photovoltammetry (LSPV). The band gap energy and transition type were determined from optical absorbance data. PXRD results showed the formation of polycrystalline orthorhombic crystal structure of SnSe₀.₅S₀.₅ with strong (111) being the most intense orientation. SEM micrographs revealed the morphological nature of the deposit which is depended on the deposition condition. EDAX results showed that less sulfur was deposited for the samples. All films prepared in this study showed rectifying behaviour in cathodic polarization regime signifying p-type conduction. A good quality tin seleno sulphide film was obtained from equal volume mixture of 0.005 M Sn-EDTA, 0.0025 M Na2Se03 and 0.0025 M Na₂S₂O₃ solutions at potential -0.70 V in the presence of 0.010 MEDTA. Binary phase of SnS2 was found present in films deposited at more negative potentials than -0.70 V. The presence of EDT A has improved the quality of the samples. Increasing the bath temperature improve the crystallinity, morphology and photosensitivity of the films. The electrodeposition is most suitable to be carried out at 60°C. However, when bath temperature is increased to 70°C, the grain size and surface coverage of the deposits was reduced, which may due to dissolution of deposit because of high temperature. Increasing the deposition time allowed more material to be deposited onto the substrate and the most suitable deposition time was found to be 60 min. pH 1.0 was fovund to be the optimum condition to prepare tin seleno sulphide. The photosensitivity and crystallinity of the films decreased when pH 1.5 and pH 2.0 was used. Annealing at 400 DC for 20 min could improve the crystallinity of the films. The energy gap is around 1.20 eV with indirect transition type as determined by optical absorption data.